2015
DOI: 10.5020/18061230.2015.p402
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à realização de mamografia e exame citopatológico

Abstract: PREVALÊNCIA E FATORES ASSOCIADOS À REALIZAÇÃO DE MAMOGRAFIA E EXAME CITOPATOLÓGICOPrevalence and factors associated with the performance of mammography and pap smear test Prevalencia y factores asociados a la realización de mamografía y examen histopatologico RESUMO Objetivo: Estimar a prevalência e os fatores associados à realização de mamografia e exame citopatológico em mulheres da cidade de Maringá, Paraná. Métodos: Estudo transversal, de base populacional, feito com 345 mulheres com idade superior a 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…With regards to mammogram rates, the Federative Unit of Paraná showed the highest one in Brazil, which goes according to the study by Lopes et al, (2015). Even though the State of Paraná has a number of mammography devices above the recommended level, these authors also found (Lopes et al, 2015) an increase in mortality from breast cancer, possibly due to poor distribution of devices, difficulties in population access to mammograms, or late screening and diagnosis. In addition to Paraná, the Units with the lowest rate of mammograms were Amapá, Distrito Federal and Piauí.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…With regards to mammogram rates, the Federative Unit of Paraná showed the highest one in Brazil, which goes according to the study by Lopes et al, (2015). Even though the State of Paraná has a number of mammography devices above the recommended level, these authors also found (Lopes et al, 2015) an increase in mortality from breast cancer, possibly due to poor distribution of devices, difficulties in population access to mammograms, or late screening and diagnosis. In addition to Paraná, the Units with the lowest rate of mammograms were Amapá, Distrito Federal and Piauí.…”
Section: Discussionmentioning
confidence: 92%
“…However, this group had a lower average percentage of women under 50 years of age and a lower average number of years of schooling. One possible explanation for this result is the difficulty in accessing the test, as stated by Rodrigues et al, (2019) and Lopes et al, (2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show social inequalities in access to breast cancer screening (8)(9)(10)(11)(12)(13)(14) . Black and brown (pardo) women (8) , with a low level of education (8,(10)(11)13) , who were single or living without a partner (8,10,15,16) , who smoked (8) and did not have health insurance (12)(13)(14) had mammographies less often. Additionally, studies with small samples (8,12) have shown that unhealthy behaviors, such as insufficient physical activity level and low intake of fruits and vegetables, may be associated with non-adherence to mammography screening.…”
Section: Introductionmentioning
confidence: 99%